Intra-articular hyaluronan is without clinical effect in knee osteoarthritis: a multicentre, randomised, placebo-controlled, double-blind study of 337 patients followed for 1 year. Issue 6 (6th May 2010) - Jørgensen, Anette; Stengaard-Pedersen, Kristian; Simonsen, Ole; Pfeiffer-Jensen, Mogens; Eriksen, Christian; Bliddal, Henning; Pedersen, Niels Wisbech; Bødtker, Søren; Hørslev-Petersen, Kim; Snerum, Lennart Ørtoft; Egund, Niels; Frimer-Larsen, Helle
Abstract : Objective: To examine the long-term efficacy and safety of five intra-articular injections with hyaluronan in knee osteoarthritis. Methods: A multicentre, randomised, placebo-controlled double-blind study of 337 patients fulfilling the American College of Rheumatology (ACR) criteria for knee osteoarthritis (clinical and laboratory) and with a Lequesne algofunctional index score (LFI) of 10 or greater. Patients received a hyaluronan product (sodium hyaluronate; Hyalgan) (n=167) or saline (n=170) intra-articularly weekly for 5 weeks and were followed up to 1 year. Time to recurrence was the primary efficacy parameter. LFI, pain on walking 50 m based on visual analogue scale (VAS pain 50 m), paracetamol consumption, patients' global assessment, Nottingham health profile, joint effusion and number of responders were secondary efficacy parameters. The efficacy parameters were analysed by intention to treat (ITT) and per protocol (PP). All adverse events (AE) were recorded as safety parameters. Results: Time to recurrence showed no significant treatment effect (ITT analysis, p=0.26). Change from baseline in LFI and VAS pain 50 m for the ITT population showed no treatment effect. Paracetamol consumption, patients' global assessment, responder rates and AE displayed no significant difference between treatment groups, analysed by both ITT and PP. Treatment compliance was 95% in the hyaluronan group and 99% in the placebo group. No safety problems were registered. Conclusion: In patients fulfilling the ACR criteria for osteoarthritis of the knee with moderate to severe disease activity (LFI ≥10), five intra-articular injections of hyaluronan did not improve pain, function, paracetamol consumption or other efficacy parameters 3, 6, 9 and 12 months after the treatment.